220 mutation in the hemagglutinin of avian influenza A (H7N9) virus alters antigenicity during vaccine strain development. Issue 3 (4th March 2018) - Liu, Liqi; Lu, Jian; Li, Zi; Zhou, Jianfang; Guo, Junfeng; Li, Xiyan; Liu, Jia; Shu, Yuelong; Wang, Dayan
ABSTRACT: Since the first confirmed case of H7N9 infection was reported in China, there have been five epidemic waves of human H7N9 infections between 2013 and 2017. The fifth wave differed from the previous four waves in that highly pathogenic avian influenza (HPAI) H7N9 viruses with multiple basic amino acids at the cleavage site were detected in humans, poultry and environmental samples. The HPAI H7N9 viruses were genetically and antigenically distinct from previous H7N9 viruses. Therefore, a new candidate vaccine virus(CVV) derived from a HPAI A/Guangdong/17SF003/2016-like virus was proposed by the World Health Organization(WHO). According to the WHO recommendations, we constructed a new CVV using reverse genetic technology, with a (6+2) gene constitution. The (6+2) reassortant virus possessed hemagglutinin(HA) with multiple basic amino acids removed and the neuraminidase from A/Guangdong/SF003/2016 in a high-yield A/Puerto Rico/8/34 virus backbone. Sequence analysis confirmed that no mutations had occurred in the HA of V1E1(the initial CVV rescued in Vero cells and followed by passage in eggs), but a mixture of arginine (R)/glycine (G)/isoleucine (I) was detected at position 220 (H3 numbering) in the HA of V1E2 to V1E5 with different percentages. Furthermore, V1E5 showed improved growth characteristics and immunogenicity compared with V1E1, and retained low pathogenicity in chickens and chicken embryos, but the mutation changed its antigenicity. Our study indicates that antigenic changes should be closely monitored during the development of H7N9 CVV in eggs. Additionally, although V1E5 changes the antigenicity, the antisera had some reactivity to previous H7N9 CVVs.